ANESTHETIC MANAGEMENT AND INTENSIVE CARE IN THE PATIENTS WITH PULMONARY HYPERTENSION ASSOCIATED WITH LEFT HEART DISEASES - A. E. BAUTIN; A. V. KSENDIKOVA; A. S. YAKOVLEV; A. O. MARICHEV; N. R. ABUTALIMOVA; L. I. KARPOVA; A. M. RADOVSKY; V. V. OSOVSKIKH (Вестник анестезиологии и реаниматологии, 2019)
Nowadays, the term "pulmonary hypertension" (PH) means a pathophysiological condition that may involve multiple clinical conditions and complicate the majority of cardiovascular and respiratory diseases. Clinical classification identifies 5 groups of pulmonary hypertension. This review focuses on group 2 - pulmonary hypertension due to left heart disease (PH due to LHD). In the general structure it takes about 80%. In routine practice, the contribution of this pathology to main disease is often underestimated, which can lead to increased mortality. The purpose of the literature review is to systematize and provide anesthesiologists with information on modern approaches to the diagnosis and treatment of PH due to LHD. The review presents data of the epidemiology and pathogenesis of this condition, describes the key concepts of adequate anesthetic management and effective intensive treatment of pulmonary hypertension in patients with left heart diseases.